AGILE observations of the ultra-luminous GRB 221009A - Piano Giovanni; Foffano Luca; Tavani Marco (EPJ Web of Conferences)
The ultra-luminous, long-duration transient event GRB 221009A was detected by several observatories - as the most luminous gamma-ray burst ever observed - from radio to VHE gamma rays, up to tens of TeV. AGILE detected an extraordinary incoming flux of hard X-ray and high-energy gammaray photons during this unprecedented event. The high-energy emission (from tens of keV up to GeV energies) has been recorded by the AGILE detectors with an almost-continuous time coverage, monitoring the transition between the prompt and the afterglow phase, up to ~20 ks after the onset of the GRB. AGILE time-resolved spectra and light curves are presented in a multi-frequency context, focused on the observed high-energy component of this intense GRB. The AGILE simultaneous hard-X/gamma-ray observations during the key phases of the burst will be crucial to give robust constraints to the physical evolution of the GRB’s high-energy emission.